Apple polyphenol extracts prevent damage to human gastric epithelial cells in vitro and to rat gastric mucosa in vivo. (11th January 2005) - Graziani, G; D'Argenio, G; Tuccillo, C; Loguercio, C; Ritieni, A; Morisco, F; Del Vecchio Blanco, C; Fogliano, V; Romano, M
Abstract : Background: Fresh fruit and vegetables exert multiple biological effects on the gastrointestinal mucosa. Aim: To assess whether apple extracts counteract oxidative or indomethacin induced damage to gastric epithelial cells in vitro and to rat gastric mucosa in vivo. Methods: Apple extracts were obtained from freeze dried apple flesh of the "Annurca" variety. Cell damage was induced by incubating MKN 28 cells with xanthine-xanthine oxidase or indomethacin and quantitated by MTT. In vivo gastric damage was induced by indomethacin 35 mg/kg. Intracellular antioxidant activity was determined using the (2, 2′-azinobis (3-ethylbenzothiazolin-6-sulfonate) method. Malondialdehyde intracellular concentration, an index of lipid peroxidation, was determined by high pressure liquid chromatography with fluorometric detection. Results: (1) Apple extracts decreased xanthine-xanthine oxidase or indomethacin induced injury to gastric epithelial cells by 50%; (2) catechin or chlorogenic acid (the main phenolic components of apple extracts) were equally effective as apple extracts in preventing oxidative injury to gastric cells; and (3) apple extracts (i) caused a fourfold increase in intracellular antioxidant activity, (ii) prevented its decrease induced by xanthine-xanthine oxidase, (iii) counteracted xanthine-xanthine oxidase induced lipid peroxidation, and (iv) decreased indomethacin injury to the rat gastric mucosa by 40%. Conclusions: Apple extracts prevent exogenous damage to human gastric epithelial cells in vitro and to the rat gastric mucosa in vivo. This effect seems to be associated with the antioxidant activity of apple phenolic compounds. A diet rich in apple antioxidants might exert a beneficial effect in the prevention of gastric diseases related to generation of reactive oxygen species.